Ukrainian Refugees in Switzerland: A research synthesis of what we know - Didier Ruedin (SocArXiv, 2025)
The objective of this research synthesis is to collect and summarize the research literature on Ukrainian refugees in Switzerland. This is done through a systematic review, mostly in the form of a narrative review and with statistical indicators that are synthesized. There is a wide range of evidence on Ukrainian refugees in Switzerland and their integration, although substantive and systematic gaps remain. The review provides a brief historical background, looks at the demographic composition of Ukrainian refugees in Switzerland, discusses economic integration, housing, education, social integration, crime and safety, health and well-being, and attitudes to Ukrainian refugees. Much less is known about cultural integration and political participation. Given the size of the population and the ongoing war in Ukraine, more research on Ukrainian refugees is warranted, particularly in the direction of successful integration in a context where return seems increasingly unlikely — although dual-intent remains the official focus —, and in areas beyond economic integration that affect well-being and intentions to return.
Additional information: Updates will be available at https://osf.io/preprints/socarxiv/tcnhx
Keywords: F22; O15; J15; J61; K37; 330; Ukraine; Switzerland; attitudes; demographics; economics; education; health; housing; integration; media; participation; literature review; refugees